RADIOGRAPHIC AND CLINICAL ASSESSMENT OF TWO CANALS IN THE MAXILLARY SECOND PREMOLAR
Background: The second premolar is one of the teeth which are crucial both aesthetically as well as functionally and one of the most commonly endodontically treated tooth. Aim of the study was to assess the number of canals in maxillary second premolar by clinical and radiographic evaluation in Pakistani sub population. It was a cross sectional study conducted in Endodontic Department of Rehmat Memorial Dental Teaching Hospital, Abbottabad, from January 2019 to January 2020. Method: One hundred and five patients were selected for the study, based on non-probability sampling technique. All patients were examined clinically by exploration of pulp chamber followed by intra oral peri-apical radiograph to verify the clinical exploration of canals. Result: One hundred and five patients (46 males (43.8%) and 59 females (56.2%)